Avaliação dos pré-tratamentos por ultrassom e micro-ondas na obtenção de bio-óleo rico em fenóis - Bispo, Diego Fonseca (2023)
The present study aimed to investigate the effect of ultrasonic and microwave pretreatments on obtaining bio-oil rich in phenols from pyrolysis of grape seed biomass. The pre-treatments were carried out based on a Box-Behnken plan, which evaluated the impact of various variables such as temperature, pH, and potency for the microwave treatment and temperature, time, and pH for the ultrasound treatment. Under the best conditions for microwave pre-treatment (160 °C, pH 12, and 300 W), the statistical model predicted a yield of phenols in the bio-oil of 131.41 mg/L, representing a 68.67% increase compared to untreated biomass. For ultrasound pretreatment, the optimal condition suggested by the model (pH 12, 80 °C, and 1.5 h) resulted in a yield of 194.90 mg/L, representing a 98.40% increase in phenol yield compared to untreated biomass. Analyses of the reducing sugar content in the aqueous fractions of the two pre-treatments showed that increasing the temperature and using severe pH conditions (2 or 12) favored the hydrolysis of cellulose and hemicellulose, enriching the biomass in lignin. From an energy consumption standpoint, ultrasound treatment had a better yield/energy consumption ratio, consuming 80% more energy but offering a yield 2.19 times higher than that predicted for using microwaves.